Upaya Meningkatkan Kemampuan Berbahasa Anak Melalui Penggunaan Boneka Tangan Pada Kegiatan Bercerita Tema Keluargaku Di Kelompok B Ra Al – Falah - Asnayah, Asnayah; Erfantinni, Imro'atul Hayyu; Febriani, Roiyan One (Jurnal Penelitian Anak Usia Dini, 2023)
This research is based on the following issues: (1) What is the level of language proficiency of children in Group B at RA Al-Falah before using hand puppet media? (2) How is the implementation of storytelling activities using hand puppet media in Group B at RA Al-Falah? (3) What is the level of language proficiency of children in Group B at RA Al-Falah after using hand puppet media? The objectives of this research are to determine: (1) The language proficiency of children in Group B at RA Al-Falah before using hand puppet media. (2) The implementation of storytelling activities using hand puppet media in Group B at RA Al-Falah. (3) The language proficiency of children in Group B at RA Al-Falah after using hand puppet media. This research employs a classroom action research with two cycles. Each cycle consists of four stages: planning, action, observation, and reflection. The target of this research is students in Group B, with a total of 10 children. The research results show that the implementation of learning with the hand puppet method in storytelling activities can improve the language proficiency of children in Group B. The research findings indicate an increase in the percentage. In Cycle I, the percentage of children in listening skills was 42% with a criteria of very poor, and in Cycle II, the listening skills increased to 85% with a criteria of excellent. In Cycle I, the percentage of children in speaking was 42% with a criteria of very poor, and in Cycle II, it increased to 85% with a criteria of excellent. In Cycle I, the percentage of children in reading words was 36% with a criteria of very poor, and in Cycle II, it increased to 79% with a criteria of good.